REPRESENTASI MASKULINITAS PEREMPUAN DALAM FILM SEPERTI DENDAM, RINDU HARUS DIBAYAR TUNTAS: ANALISIS SEMIOTIKA JOHN FISKE - Astutik, Fitri; Setiadi, Tatak (Universitas Negeri Surabaya, 2024)
This study aims to find out the forms of representation of female masculinity from films Vengeance Is Mine, All Others Pay Cash. The subject of this study is 10 film scenes that have been curated and categorized according to the characteristics of the form of female masculinity. This study uses John Fiske's semiotic analysis which has three levels; reality, representation, and ideology. The results of this study show that the female character in the film, Iteung, depicts the masculinity side of women. The form of masculinity representation that emerges is that women do extreme work, women hold back sad emotions, are firm and brave in making decisions, women take revenge. It is possible to understand how the film Vengeance Is Mine, All Others Pay Cash not only serves as entertainment, but also as a medium to criticize and challenge social constructions about gender, as well as to expand the representation of women in culture.